Buletin Peternakan : Analisis Ekonomi Usaha Tanaman Pangan dan Kambing Kosta di Kecamatan Carita Kabupaten Pandeglang, Banten - Supardi Rusdiana, Endang Sutedi (Peternakan UGM, 2016)
The purpose of this research was to determine the economic analysis of crop and livestock enterprises Costa goat. The experiment was conducted in the village of Sukarame District of Pandeglang Banten Carita. Interviews to 20 farmers the agro-ecosystem crops and livestock farmer Costa goat using questionnaires.